Organic Diode Rectifiers Based on a High‐Performance Conjugated Polymer for a Near‐Field Energy‐Harvesting Circuit. Issue 46 (20th October 2017) - Higgins, Stuart G.; Agostinelli, Tiziano; Markham, Steve; Whiteman, Robert; Sirringhaus, Henning
Abstract: Organic diodes manufactured on a plastic substrate capable of rectifying a high‐frequency radio‐frequency identification signal (13.56 MHz), with sufficient power to operate an interactive smart tag, are reported. A high‐performance conjugated semiconductor (an indacenodithiophene‐benzothiadiazole copolymer) is combined with a carefully optimized architecture to satisfy the electrical requirements for an organic‐semiconductor‐based logic chip. Abstract : A high‐performance conjugated polymer is shown to create fast organic rectifiers, which can be used in a near‐field energy‐harvesting circuit. The performance of this circuit is sufficient to power an interactive smart tag from a 13.56 MHz near‐field communication source.